Crystallographic texture of hot rolled uranium-molybdenum alloys - Guilherme Fernandes Nielsen; Nathanael Wagner Sales Morais; Nelson Batista de Lima (Brazilian Journal of Radiation Sciences)
The uranium molybdenum (U-Mo) alloys have potential to be used as low enriched uranium nuclear fuel in research, test and power nuclear reactors. U-Mo alloy with composition between 7 and 10 wt% molybdenum shows excellent body centered cubic phase (γ phase) stabilization and presents a good nuclear fuel testing performance. Hot rolling is commonly utilized to produce parallel fuel plate where it promotes the cladding and the fuel alloy bonding. The mechanical deformation generates crystallographic preferential orientation, the texture, which influences the material properties. This work studied the texture evolution in hot rolled U-Mo alloys. The U7.4Mo and U9.5Mo alloys were melted in a vacuum induction furnace, homogenized at 1000°C for 5 h and then hot rolled at 650°C in three height reductions: 50, 65 and 80%. The crystalline phases and the texture were evaluated by X-ray diffraction (XRD). The as-cast and processed alloys microstructures were characterized by optical and electronic microscopies. The as-cast, homogenized and deformed alloys have γ phase. It was found microstructural differences between the U7.4Mo and U9.5Mo alloys. The homogenized treatment showed effective for microsegregation reduction and were not observed substantial grain size increasing. The deformed uranium molybdenum alloys presented α, γ, θ texture fibers. The intensity of these texture fibers changes with deformation step.